Growth Patterns of HIV-Exposed and -Unexposed Infants in African Countries: A Systematic Review and Meta-Analysis - Perpetua Modjadji; Kabelo Mokgalaboni; Wendy N. Phoswa; Tebogo Maria Mothiba; Sogolo L. Lebelo (Children)
Background/Objectives: The purpose of this study is to understand the prevalence and odds of poor growth patterns among HIV-exposed but uninfected (HEU) versus HIV-unexposed (HUU) infants in the era of antiretroviral therapy (ART) and prevention of mother-to-child transmission (PMTCT) in Africa. Methods: We reviewed and meta-analyzed studies on growth patterns among HEU versus HUU infants in Africa. Evidence was gathered from the PubMed and Scopus databases following PRISMA guidelines. We independently evaluated the quality of included studies using Newcastle Ottawa guidelines. Data analysis was performed using an online meta-analysis tool, and the results are reported as odds ratios (OR) and prevalence with 95% confidence intervals (CI). Results: A total of 17 studies met the inclusion criteria for this review. The odds of stunting were significantly higher among HEU infants compared to HUU infants, with an odds ratio of 1.56 (95% CI: 1.23–1.97; p < 0.01). The pooled prevalence of stunting was 25% (95% CI: 17–33%) in HEU infants and 19% (95% CI: 12–26%) in HUU infants. In contrast, no significant differences were observed for underweight and wasting. The odds of being underweight in HEU infants compared to HUU was 0.85 (95% CI: 0.47–1.56; p = 0.60), with a pooled prevalence of 11% (95% CI: 5–17%) in HEU and 14% (95% CI: 5–24%) in HUU. Similarly, the odds of wasting were 1.10 (95% CI: 0.78–1.56; p = 0.58), with a pooled prevalence of 9% (95% CI: 3–14%) in HEU and 7% (95% CI: 3–12%) in HUU. Conclusions: Stunting was the most prevalent growth deficit among HEU infants compared to their HUU counterparts, with no significant differences observed in the rates of underweight and wasting. To improve postnatal growth outcomes, especially in the evolving landscape of HIV treatment and prevention, efforts should focus on educating and supporting mothers living with HIV.